Genetic Characterization of Swamp Eel of Bangladesh Through Dna Barcoding and Rapd Techniques (Journal of the Asiatic Society of Bangladesh, Science, 2020)
The freshwater air-breathing swamp eel Monopterus spp. are native to the freshwater of Bangladesh and throughout the Indian subcontinent. To identify the different swamp eel species and to check the genetic diversity among them, a total of twelve swamp eel specimens were collected from four districts (Tangail, Bogura, Bagerhat and Sylhet) representing the four division of Bangladesh. The extracted DNA from twelve fish samples was amplified by the PCR technique for DNA barcoding and RAPD analysis. Among 12 specimens, 8 specimens showed a 95-100% similarity with M. cuchia species published in the NCBI GenBank database and BOLD system. The studied mct3 (collected from Tangail region), mcs1, mcs2 and mcs3 (collected from Sylhet region) specimens showed about 83% homology with Ophisternon sp. MFIV306-10 as per BLAST search; whereas BOLD private database showed 99% similarity with Ophisternon bengalense (Bengal eel). From the phylogenetic tree analysis, 8 samples were clustered with M. cuchia and 4 samples showed similarity with Ophisternon sp. MFIV306-10 and Ophisternon bengalense _ANGBF45828-19. In RAPD-PCR based analysis, it was found that the maximum genetic distance (1.6094) was observed between mcba2 and mcs3, while between mct1 and mct2, the minimum genetic distance was 0.000. A total of 192 bands, of which 35 were polymorphic with 17.88% polymorphisms among swamp eel species and the size of the amplified DNA fragments ranged from 250 to 1800 bp. The information on DNA barcoding and RAPD analysis help measure the genetic diversity among swamp eel species, ensure the reliability of the published taxonomic information, and initiate proper management programs to conserve these vulnerable species to meet future export demand.J. Asiat. Soc. Bangladesh, Sci. 46(2): 117-131, December 2020